Tackling the COVID elective surgical backlog: Prioritising need, benefit or equality? - Pugh, J; Seah, M; Carr, A; Savulescu, J (SAGE Publications, 2023)
The National Health Service (NHS) in the UK is currently facing a significant waiting list backlog following the disruption of the COVID-19 pandemic, with millions of patients waiting for elective surgical procedures. Effective treatment prioritisation has been identified as a key element of addressing this backlog, with NHS England's delivery plan highlighting the importance of ensuring that those with ‘the clinically most urgent conditions are diagnosed and treated most rapidly’. Indeed, we describe how the current clinical guidance on prioritisation issued by The Federation of Surgical Specialty Associations serves this aim. However, whilst there are strong reasons to prioritise elective surgery in accordance with clinical need, we argue that it would be a mistake to assume that prioritisation in accordance with clinical need requires only a clinical or scientific judgement. The understanding of clinical need that we choose to employ in a prioritisation system will be grounded by some key ethical judgements. Moreover, we may also have to make trade-offs between addressing clinical need, safeguarding equality, and achieving other benefits. As the UK faces up to the backlog, it is important that surgical prioritisation guidelines enshrine a broad range of values that we believe ought to determine access to care in non-emergency circumstances. Our analysis suggests that the current approach to prioritisation is not a sufficiently nuanced way of balancing the different moral values that are operative in this context.